Analisis Potensi Bahaya dan Manajemen Risiko pada Stasiun Evaporasi Dengan Metode Hazard and Operability (Hazop) Pabrik Gula PT XYZ - Saadillah, Dinu; Nadhirah, Aulia; Al Ardi, Aditya; Hardiyani, Rini (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
Occupational safety and health play a crucial role in controlling industrial operational risks, particularly in sugar mill evaporation stations. The high-temperature and high-pressure evaporation process of sugarcane juice has the potential to cause various hazards, including leaking pipes, high temperatures around the evaporation station, noise, and steam emissions. Identification of potential hazards and analysis of occupational accident risks are required using the Hazard and Operability Study (Hazop) method. This study uses a quantitative descriptive approach, including field observations, in-depth interviews, and supporting documentation. Likelihood and severity matrices are used in the risk assessment to determine the risk level of various hazards. The results of the study indicate nine potential hazards, with an extreme risk of 11%, a high risk of 50%, and a moderate risk of 22%. This extreme risk potential hazard occurs due to leaks in high-pressure pipes during the steam flow to the evaporator. Risk management can be implemented through risk mitigation, including the installation of safety valves, routine inspections, ventilation and drainage systems, the use of personal protective equipment (PPE), and SMK3 training. An effective hazard control strategy can be achieved by systematically implementing Hazop analysis to create a safe and accident-free work environment.